2020
DOI: 10.3390/jcm9082381
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Osteosarcopenia and Frailty in Patients with Chronic Liver Disease

Abstract: Osteosarcopenia and frailty have a negative health impact on an aging society. This cross-sectional study aimed to investigate the clinical characteristics and relationship of osteosarcopenia and frailty in 291 patients with chronic liver disease (CLD), who comprised 137 males and 154 females, with a median age of 70.0 years. Sarcopenia was diagnosed according to the Japan Society of Hepatology criteria. Bone mineral density was measured using dual-energy X-ray absorptiometry. Frailty was defined by five param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…However, literature on the prevalence and clinical implications of osteosarcopenia in chronic liver disease remains limited. Seaki et al reported that the prevalence of osteosarcopenia was approximately 20% in patients with chronic liver disease, with osteoporosis increasing the risk of vertebral fracture in these patients ( Table 3 ) [ 189 , 190 ].…”
Section: Osteosarcopeniamentioning
confidence: 99%
“…However, literature on the prevalence and clinical implications of osteosarcopenia in chronic liver disease remains limited. Seaki et al reported that the prevalence of osteosarcopenia was approximately 20% in patients with chronic liver disease, with osteoporosis increasing the risk of vertebral fracture in these patients ( Table 3 ) [ 189 , 190 ].…”
Section: Osteosarcopeniamentioning
confidence: 99%
“…Of note, bone disease impacts trabecular bone (i.e., the lumbar spine) more significantly than cortical bone (i.e., femur neck) because of relatively increased turnover in the trabecular bone (38). Bone disease, like sarcopenia, is closely associated with frailty; it also places cirrhotic patients at increased risk for fractures, specifically vertebral fractures, and associated complications such as increased hospital length of stay and 30-day mortality (38,40,41). The risk of post-fracture adverse events was significantly elevated if patients had other clinical complications of cirrhosis, such as ascites (41).…”
Section: Bone Abnormalitiesmentioning
confidence: 99%
“…Although both sarcopenia and osteoporosis affect different organs and tissues, they are closely interrelated through common factors, such as genetic factors, endocrine hormones, nutritional status and daily activities [ 27 , 28 ]. LC patients with both osteoporosis and sarcopenia (i.e., osteosarcopenia) have elevated risk of vertebral fractures [ 26 , 29 ].…”
Section: Liver Cirrhosis and Sarcopenia: Pathophysiology And Prognosismentioning
confidence: 99%